Effects of mindfulness training on resilience, self-confidence and emotion regulation of elite football players: The mediating role of locus of control - Oguntuase, S. B.; Sun, Y. (Asian Journal of Sport and Exercise Psychology, 2022)
This study investigated effects of mindfulness training on resilience, self-confidence and emotion regulation of elite football players as well as mediating role of locus of control. The study recruited 34 participants which were assigned into experimental (n=17) and control (n=17) groups. Age ranged between 16 and 32years (M age = 22.6years, SD = 1.47). The experimental group received 8 weeks mindfulness acceptance commitment (MAC) intervention program, while control group received no intervention. Participants completed Five Facet Mindfulness Questionnaire (FFMQ), The Connor-Davidson Resilience scale (CD-RISC), Trait Sport Confidence Inventory (TSCI), Emotion Regulation Questionnaire (ERQ) and Adapted Levenson Multidimensional Locus of control scales (ALMLC). Both groups completed the questionnaire at pre-test and post-test evaluation. Descriptive data employed mean and standard deviation, while Structural Equation Modelling (SEM) of S?rbom's method (alternative to analysis of covariance) was used for analysis of hypothesis. Finding of the study showed that there is significant direct and indirect effect of mindfulness acceptance commitment on resilience, self-confidence and emotion regulation on elite football players. The findings further showed that there is significant difference between the pre-test scores and post-test scores of intervention group and control group. The intervention group mean scores on resilience, self-confidence and emotion regulation are higher than the control group counterparts. This shows that MAC program is effective in increasing resilience, self-confidence and emotion regulation of elite football players concurrently which in turn could improve performance and attain success.